Street vendors in Tacloban City an urban management challenge - Calonia, Aivan Lloyd M.; Catarong, Jessa Veil D.; Grisola, Juvy Ann J.; Liem, Jennifer C.; Moreno, Jessadale G. (2016)
This research analyzes the state of street vendors in Tacloban City. This research confirms the perennial problems caused by street vending in the city. This study also verifies that the street vendors are not fully aware of the rules and regulations implemented by the Mayor Alfred's Social Action (MASA) Office and that the federation is not empowered. The weak implementation of the rules and regulations results to the rise of perennial problems caused by the street vendors; street congestion, waste mismanagement and threat to safety of pedestrians. Thus, the street vendors, federation and implementing body should work hand in hand towards preservation of livelihood and a better Tacloban City as a Highly Urbanized City (HUC).